Untangled : guiding teenage girls through the seven transitions into adulthood - Damour, Lisa, 1970- (New York : Ballantine Books, 2016)
Dr. Damour draws on decades of experience and the latest research to reveal the seven distinct -- and absolutely normal -- developmental transitions that turn girls into grown-ups, including Parting with Childhood, Contending with Adult Authority, Entering the Romantic World, and Caring for Herself. Providing realistic scenarios and advice on how to engage daughters in smart, constructive ways, Untangled gives parents a broad framework for understanding their daughters while addressing their most common questions, including: My thirteen-year-old rolls her eyes when I try to talk to her, and only does it more when I get angry with her about it. How should I respond? -- Do I tell my teen daughter that I'm checking her phone? -- My daughter suffers from test anxiety. What can I do to help her? -- Where's the line between healthy eating and having an eating disorder? -- My teenage daughter wants to know why I'm against pot when it's legal in some states. What should I say? -- My daughter's friend is cutting herself. Do I call the girl's mother to let her know? Untangled helps mothers and fathers understand, connect, and grow with their daughters. When parents know what makes their daughter tick, they can embrace and enjoy the challenge of raising a healthy, happy young woman.
Parting with childhood -- Joining a new tribe -- Harnessing emotions -- Contending with adult authority -- Planning for the future -- Entering the romantic world -- Caring for herself.
Includes bibliographical references (pages [283]-309) and index.
Keywords: Teenage girls -- Psychology; Adolescence; Adulthood; Adolescent psychology